Ethnography & personhood : notes from the field - Meister, Michael W. (Jaipur : Rawat Publications, 2000)
With reference to India.
Includes bibliographical references and index.
Keywords: ETHNOLOGY -- FIELDWORK -- INDIA; ETHNOLOGY -- INDIA -- METHODOLOGY; RITES AND CEREMONIES -- INDIA; INDIA -- SOCIAL LIFE AND CUSTOMS